Participation of HIV prevention programs among men who have sex with men in two cities of China-a mixed method study - Ma Wei; Raymond H Fisher; Wilson Erin C; McFarland Willi; Lu Hongyan; Ding Xianbin; Lu Rongrong; Ma Xiaoyan; Xia Dongyan; Xu Jing; He Xiong; Feng Liangui; et al. (BMC, 2012)
Abstract Background Although various HIV prevention programs targeting men who have sex with men (MSM) are operating in China, whether and how these programs are being utilized is unclear. This study explores participation of HIV prevention programs and influencing factors among MSM in two cities in China. Methods This is a mixed-method study conducted in Beijing and Chongqing. A qualitative study consisting of in-depth interviews with 54 MSM, 11 key informants, and 8 focus group discussions, a cross-sectional survey using respondent-driven sampling among 998 MSM were conducted in 2009 and 2010 respectively to elicit information on MSM's perception and utilization of HIV prevention programs. Qualitative findings were integrated with quantitative multivariate factors to explain the quantitative findings. Results Fifty-six percent of MSM in Chongqing and 75.1% in Beijing ever participated in at least one type of HIV prevention program (P=0.001). Factors related to participation in HIV prevention programs included age, ethnicity, income, HIV risk perception, living with boyfriend, living in urban area, size of MSM social network, having talked about HIV status with partners, and knowing someone who is HIV positive. Reasons why MSM did not participate in HIV prevention programs included logistical concerns like limited time for participation and distance to services; program content and delivery issues such as perceived low quality services and distrust of providers; and, cultural issues like HIV-related stigma and low risk perception. Conclusions The study shows that there is much room for improvement in reaching MSM in China. HIV prevention programs targeting MSM in China may need to be more comprehensive and incorporate the cultural, logistic and HIV-related needs of the population in order to effectively reach and affect this population's risk for HIV.